THE IMPORTANT ROLE OF MOTIVATION IN FOREIGN LANGUAGE LEARNING: A REVIEW - Alpino Susanto (Universitas Singaperbangsa Karawang, 2018)
Motivation has been called the “neglected heart” of English language teaching (Rost 2006). Some teachers may forget that all of the learning activities are filtered through the students’ motivation (Dörnyei 2001). In this sense, students control the flow of the classroom. Without student motivation, there is no pulse; there is no life in the class. When teachers learn to incorporate direct approaches to generate student motivation in their teaching, they may become happier and more successful teachers. The issue of motivation, particularly in English as Foreign language Learning (EFL) settings, is so important. Other considerations about teaching methodology seem to pale in comparison. It is important to think about motivation as the essence of English language teaching because of the stark realities of learning English for most of foreign language learners/students.